2012
DOI: 10.5194/hess-16-2347-2012
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the modified SCS-CN and RUSLE models to simulate hydrological effects of restoring vegetation in the Loess Plateau of China

Abstract: Abstract. Predicting event runoff and soil loss under different land covers is essential to quantitatively evaluate the hydrological responses of vegetation restoration in the Loess Plateau of China. The Soil Conservation Service curve number (SCS-CN) and Revised Universal Soil Loss Equation (RUSLE) models are widely used in this region to this end. This study incorporated antecedent moisture condition (AMC) in runoff production and initial abstraction of the SCS-CN model, and considered the direct effect of r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 56 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…However, it was found in the scientific literature (Todisco et al, 2009;Bagarello et al, 2008;Risse et al, 1993) that the USLE/RUSLE model, and similarly (Tiwari et al, 2000) process-oriented models (e.g., Water Erosion Prediction Project, WEEP, Flanagan et al, 1995), tends to overestimate (underestimate) soil losses for low (high) erosive events. Foster et al (1982) noted that the USLE model is somewhat unsatisfactory for estimating soil loss from individual storms, and observed that including rainfall amount, rainfall intensity and runoff amount in the erosivity factor provided better performance. Foster et al (1982) also noted that erosivity factors with separate terms for rainfall and runoff erosivity were more appropriate.…”
Section: F Todisco Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was found in the scientific literature (Todisco et al, 2009;Bagarello et al, 2008;Risse et al, 1993) that the USLE/RUSLE model, and similarly (Tiwari et al, 2000) process-oriented models (e.g., Water Erosion Prediction Project, WEEP, Flanagan et al, 1995), tends to overestimate (underestimate) soil losses for low (high) erosive events. Foster et al (1982) noted that the USLE model is somewhat unsatisfactory for estimating soil loss from individual storms, and observed that including rainfall amount, rainfall intensity and runoff amount in the erosivity factor provided better performance. Foster et al (1982) also noted that erosivity factors with separate terms for rainfall and runoff erosivity were more appropriate.…”
Section: F Todisco Et Almentioning
confidence: 99%
“…Foster et al (1982) noted that the USLE model is somewhat unsatisfactory for estimating soil loss from individual storms, and observed that including rainfall amount, rainfall intensity and runoff amount in the erosivity factor provided better performance. Foster et al (1982) also noted that erosivity factors with separate terms for rainfall and runoff erosivity were more appropriate. Successively, Kinnell (1997) suggested that the sediment concentration for individual rainfall event is dependent on the event rainfall erosivity index per unit rainfall depth and developed the so-called USLE-M model, including direct measures of the runoff in the event rainfall-runoff erosivity factor (Kinnell and Risse, 1998;Kinnell, 2007Kinnell, , 2010Bagarello et al, 2011).…”
Section: F Todisco Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Should this be the case, b1 estimation procedures need to be developed. Currently, we know that, in the USLE-MM, b1 is greater than 1 but it does not exceed approximately 1.6 in central and southern Italy locations (Bagarello et al, 2008(Bagarello et al, , 2010a(Bagarello et al, , 2013a(Bagarello et al, , 2013b(Bagarello et al, , 2015a(Bagarello et al, , 2015b and it is equal to 1.55 at a Chinese experimental station (Gao et al, 2012). Therefore, it appears plausible to suppose that a single b1 value could be used in general for practical purposes.…”
Section: Modified Universal Soil Loss Equation (Musle) Usle-m and Usmentioning
confidence: 99%
“…A modified Soil Conservation Service -Curve Number (SCS-CN) model was applied by Gao et al (2012) to obtain an estimate of the plot runoff coefficient specifically usable with a USLE-MM type soil erosion model. In short, the event runoff, Qe (mm), is predicted by the following relationship: where P (mm) is total precipitation depth, lc is the initial abstraction coefficient, representing losses due to interception, surface storage and infiltration, S (mm) is the potential maximum retention, and Ms (mm) is the moisture of the soil profile before the start of the storm.…”
Section: Reference Stepsmentioning
confidence: 99%